2010
DOI: 10.1071/rd09156
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fetal and maternal instrumentation in pregnant sheep: Effect on gestation length and birthweight

Abstract: The objective was to compare gestation length in chronically instrumented (laboratory) pregnant sheep (n = 131) and in the breeding flock (n = 476) that provided the experimental sheep. In the breeding flock, gestation length was normally distributed and varied between 141 and 151 days (mean = 147 +/- 0.1 days). In the laboratory sheep, gestation length varied between 128 and 151 days (mean = 142 +/- 1 day), and was bimodal, with 35.9% delivering preterm (<141 days). To examine potential factors that contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The number of samples collected from an individual fetus ranged from 1 to 17 (mean ϭ 4.1 Ϯ 0.3) and the number of days over which sampling occurred was from 1 to 24 (mean ϭ 5.8 Ϯ 0.5) days. All operated fetuses survived until spontaneous delivery, although as reported previously (9), there was a significant incidence of preterm birth in the operated animals that was not present in the breeding flock from which the study animals were obtained. Birth weight averaged 3.84 Ϯ 0.13, 3.40 Ϯ 0.08, and 2.96 Ϯ 0.23 kg for singletons, twins, and triplets, respectively.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The number of samples collected from an individual fetus ranged from 1 to 17 (mean ϭ 4.1 Ϯ 0.3) and the number of days over which sampling occurred was from 1 to 24 (mean ϭ 5.8 Ϯ 0.5) days. All operated fetuses survived until spontaneous delivery, although as reported previously (9), there was a significant incidence of preterm birth in the operated animals that was not present in the breeding flock from which the study animals were obtained. Birth weight averaged 3.84 Ϯ 0.13, 3.40 Ϯ 0.08, and 2.96 Ϯ 0.23 kg for singletons, twins, and triplets, respectively.…”
Section: Resultssupporting
confidence: 54%
“…The breeding method and surgical and experimental procedures employed on the animals have been previously described in our study of the effect of chronic fetal instrumentation on gestational length and birth weight in sheep (9). None of the data presented in this paper were obtained during the experiments conducted on these sheep.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that surgical instrumentation of pregnant sheep results in a significant incidence of preterm birth; whereas there was no preterm birth in the breeding flock from which the sheep that were instrumented were obtained. 33 The results of this study suggested that neither the death of the operated fetus nor the shortened gestation length affected the motility characteristics of the nonoperated twins as the break points and slopes of the regression lines in the operated ewes were not different from those in the nonoperated sheep (Table 2). In contrast, the growth of the nonoperated fetuses was affected in late gestation, as the slope of the second-phase regression line was significantly less than that in the nonoperated group (Table 3).…”
Section: Results In Nonoperated and Operated Pregnant Sheepmentioning
confidence: 67%
“…Moreover, one-half of the animals were subject to fetal surgery at about 120 days of gestation. Previously we 33 and others 34 have reported the chronic instrumentation of fetal lambs is associated with a reduction in birth weight. In this study, ultrasound of the operated ewes with twins or triplets was done on fetuses not subject to surgery.…”
Section: Introductionmentioning
confidence: 76%